The pivotal role of social identification in explaining authentic leadership’s effect on team organizational citizenship behavior - Brendan Boyle; Jun Gu; Candy Ying Lu; Zhiming Cheng; Miles Yang; Rebecca J. Mitchell (PLoS ONE, 2026)
Purpose The potential for authentic leadership to influence team organizational citizenship behavior (OCB) brings questions regarding the mechanisms underpinning such an effect into focus. Drawing on the social identity approach, we propose and investigate a moderated mediation model that authentic leadership increases team members’ OCB through increased team identification and that this mediated path is contingent on members’ professional identification. Methodology We tested our model first using a causality chain design (two recall experiments with 99 and 151 working professionals respectively) and then a multi-source field survey of 343 leaders and team members from 60 healthcare teams. Findings We find support for our moderated mediation model confirming that only in multidisciplinary professional teams characterized by weak professional identification among members does authentic leadership enhance member OCB through team identification. These findings allow us to explain ambiguities in the impact of authentic leadership in multidisciplinary professional teams, particularly in critical contexts such as healthcare. Originality/Novelty We integrate social identity theory with learning from the sociology of the professions to address important gaps in our knowledge of how professional identification influences intra-team extra-role dynamics across professional boundaries. Our investigation of the mechanisms through which authentic leadership influences OCB represents a particularly novel exploration, as we argue that professional identification can differentiate between positive and negative effects of authentic leadership via team identification. The paper’s novelty lies in explicating how professional identification conditions the indirect pathway between authentic leadership and OCB.